Losartan and Eprosartan Induce a Similar Effect on the Acute Rise in Serum Uric Acid Concentration after an Oral Fructose Load in Patients with Metabolic Syndrome - Masajtis-Zagajewska, Anna; Majer, Jacek; Nowicki, Michał (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Introduction. Excessive intake of fructose increases serum uric acid concentration. Hyperuricemia induces a negative effect on atherosclerosis and inflammation. Hyperuricemia is common in patients with arterial hypertension. Several antihypertensive drugs including diuretics increase serum uric acid concentration. In contrast, the angiotensin II receptor antagonist (ARB) losartan was found to lower serum uric acid though it may increase renal excretion while other ARBs showed mostly a neutral effect. In this study, effects of two AT1 receptor antagonists losartan and eprosartan on serum uric acid changes induced by oral fructose load were directly compared. Methods. The randomized, crossover, head-to-head comparative study comprised 16 ambulatory patients (mean age 64.5±9.8 years). The patients fulfilled AHA/NHLBI 2005 criteria of metabolic syndrome. A daily single morning dose of each study drug (50 mg of losartan or 600 mg of eprosartan) was given during two 3-month periods in a random order separated by 2-week washout time. The oral fructose tolerance test (OFTT) was performed at baseline and after each two 3-onth treatment periods. Before and during OFTT, urine excretion of uric acid and creatinine was assessed in the first morning portion of urine. Blood samples for the measurement of serum uric acid and lipids were taken at baseline and 30, 60, and 120 minutes after oral intake of 75 g of fructose. Results. After 3-month treatment with eprosartan and losartan, both systolic and diastolic blood pressure decreased significantly and to a similar extent. After the treatment, serum uric acid and its baseline and postfructose urine excretion were unchanged. No significant changes of plasma lipids before and after OFTT were observed throughout the study. Conclusions. The study showed that in patients with hypertension and metabolic syndrome, both losartan and eprosartan have a neutral effect on fasting and postfructose load serum uric acid concentration and its urinary excretion. This trial is registered with NCT04954560.